Расколотая - Терри Тери (YOUNG ADULT. Стиратели судеб, 2018)
Экземпляры: аб (20180416) / Инвентарный номер: 51938 / Цена: 269.00 / Сис.шифр: И(Англ) / Авт.знак: Т 35 / ГРНТИ: 17.82.30 / ББК: 84 (4Вел)